Genetic Polymorphisms In Sea Cucumber (Holothuroidea) Using Random Amplified Polymorphic Dna (Rapd) - Kassim Shaari, Norazila (2000)
Random Amplified Polymorphic DNA (RAPD) fingerprinting was used to identify DNA-based genetic polymorphism and estimate genetic variability among 13 species of sea cucumber. It offers a rapid and efficient method for generating a new series of DNA markers in sea cucumber. Seventeen single arbitrary primers (9,10 and 1 2 nucleotides) with G+C contents 50%-80% were chosen for their utility in identifying genetic polymorphism in this study. The numbers of amplification fragments were 3-7 bands per primer that ranged in size from 80 to 1750 nucleotide base pair. Bands of the amplified DNA was scored and analyzed using the RAPDistance Package and NTSYS Program. The presence or absence of bands on the gel detects a DNA polymorphism for inter- and intra-locality studies. There were 839 types of genotype profiles from 4 locations of sea cucumber with an average of 43 in Sabah, 44 in Terengganu, 47 in Perak and 49 in Kedah. For each of the primers, 3 types of genotypes (42%) are the most frequently observed followed by 38% for 2 genotypes, 1 2% for 4 genotypes and 8% for 1 genotype.